The high bone mass phenotype is characterised by a combined cortical and trabecular bone phenotype: findings from a pQCT case-control study. - Gregson, C; Sayers, A; Lazar, V; Steel, S; Dennison, E; Cooper, C; Smith, G; Rittweger, J; Tobias, J (2013)
High bone mass (HBM), detected in 0.2% of DXA scans, is characterised by a mild skeletal dysplasia largely unexplained by known genetic mutations. We conducted the first systematic assessment of the skeletal phenotype in unexplained HBM using pQCT in our unique HBM population identified from screening routine UK NHS DXA scans. pQCT measurements from the mid and distal tibia and radius in 98 HBM cases were compared with (i) 65 family controls (constituting unaffected relatives and spouses), and (ii) 692 general population controls. HBM cases had substantially greater trabecular density at the distal tibia (340 [320, 359] mg/cm(3)), compared to both family (294 [276, 312]) and population controls (290 [281, 299]) (p<0.001 for both, adjusted for age, gender, weight, height, alcohol, smoking, malignancy, menopause, steroid and estrogen replacement use). Similar results were obtained at the distal radius. Greater cortical bone mineral density (cBMD) was observed in HBM cases, both at the midtibia and radius (adjusted p<0.001). Total bone area (TBA) was higher in HBM cases, at the distal and mid tibia and radius (adjusted p<0.05 versus family controls), suggesting greater periosteal apposition. Cortical thickness was increased at the mid tibia and radius (adjusted p<0.001), implying reduced endosteal expansion. Together, these changes resulted in greater predicted cortical strength (strength strain index [SSI]) in both tibia and radius (p<0.001). We then examined relationships with age; tibial cBMD remained constant with increasing age amongst HBM cases (adjusted β -0.01 [-0.02, 0.01], p=0.41), but declined in family controls (-0.05 [-0.03, -0.07], p<0.001) interaction p=0.002; age-related changes in tibial trabecular BMD, CBA and SSI were also divergent. In contrast, at the radius HBM cases and controls showed parallel age-related declines in cBMD and trabecular BMD. HBM is characterised by increased trabecular BMD and by alterations in cortical bone density and structure, leading to substantial increments in predicted cortical bone strength. In contrast to the radius, neither trabecular nor cortical BMD declined with age in the tibia of HBM cases, suggesting attenuation of age-related bone loss in weight-bearing limbs contributes to the observed bone phenotype.